Collaborative knowledge construction and metacognition via educational robotics - Socratous, Chrysanthos (My University, 2022)
The purpose of this study was to explore how Educational Robotics (ER) can support students’ development of metacognitive thinking as a key element for collaborative knowledge construction in Computer-Supported Collaborative Learning (CSCL) settings. The work adopts a Design-based Research (DBR) methodology, to address the development of metacognitive skills via ER while documenting design principles for successful implementations, based on collected evidence of cycles of work. The study consists of three sequential cycles in real classroom settings in primary education. The first cycle explored the use of ER in supporting collaborative knowledge construction as well as the mediating role of ER in supporting students' group metacognitive processes. The second cycle investigated the potential added value of ER in promoting students' metacognitive thinking and mathematical problem-solving. In the third cycle, the study examined how different ER learning design approaches could influence student learning. The third cycle presented differences between a structured and an unstructured ER curriculum in supporting students’ learning. Overall, findings from this dissertation provide an in-depth understanding of how ER can be used in real classroom settings for facilitating metacognitive thinking as a key element for collaborative knowledge construction. Moreover, through the analysis of different curriculum structures, the dissertation provides evidence that ER is a useful metacognitive medium whose learning benefits can be maximized through a structured curriculum design using pre-designed tasks, in combination with guided experimentation at the beginning of each session. This study is one of very few, adopting a design-based research methodology, to address the development of metacognitive skills via ER, therefore, it contributes to the scarce literature on the use of ER as tools for promoting metacognitive thinking and collaborative knowledge construction. The results of this study contribute significantly to the research conducted in the design and implementation of these interventions. Implementation of research can build on this project's elements and ground the use of ER as a metacognitive tool. The dissertation concludes with practical guidelines and implications for educators who wish to incorporate these into their curricula towards the goal of increasing metacognition and collaborative knowledge construction.
Keywords: Educational Robotics; Computer supported collaborative learning; Metacognition; Collaborative knowledge construction; Problem-solving; Classroom; Primary education; Designed-based research; Εκπαιδευτική ρομποτική; Συνεργατική μάθηση υποστηριζόμενη από υπολογιστή; Μεταγνώση; Συνεργατική οικοδόμηση της γνώσης; Επίλυση προβλήματος; Πρωτοβάθμια εκπαίδευση; Έρευνα βασισμένη στον σχεδιασμό